Challenges in Diagnosis and Treatment of Cushing Syndrome in Bilateral Macronodular Adrenal Hyperplasia - Januškevičiūtė, Edvina; Kalakauskaitė, Laura; Visockienė, Žydrūnė (Lietuvos chirurgija, 2022)
Background. Bilateral adrenal cortical hyperplasia (ACH) is one of the rare causes of adrenocorticotropic hormone (ACTH)-independent Cushing’s syndrome (CS), where lateralization of cortisol secretion and choice of treatment techniques are challenging. Percutaneous radiofrequency ablation (RFA) is a safe and effective minimally invasive treatment for benign and malignant tumors, but it is not commonly used to treat CS in bilateral ACH. Case description. A 79-year-old patient developed ACTH-independent CS with bilateral ACH. Adrenal venous sampling (AVS) showed right sided cortisol hypersecretion. Due to serious comorbidities it was decided to perform percutaneus RFA. The procedure was successful and without any complications. Hydrocortisone replacement therapy was given to manage adrenal insufficiency after the procedure. Conclusions. Percutaneous RFA is an effective minimally invasive procedure for the treatment of cortisol producing adrenal tumors. Reduction of symptoms caused by the disease has been observed after the procedure. It is also expected that hormone deficiency developed after the procedure will be transient.
Keywords: adrenal venous sampling; bilateral adrenal cortical hyperplasia; Cushing syndrome; minimally invasive surgery; radiofrequency ablation